Case report: Frontotemporal dementia and amyotrophic lateral sclerosis caused by a missense variant (p.Arg89Trp) in the valosin-containing protein gene - Miura, Shiroh; Hiruki, Shigeyoshi; Okada, Tomohisa; Takei, Satoko Itani; Senzaki, Kensuke; Okada, Yoko; Ochi, Masayuki; Tanabe, Yuki; Ochi, Hirofumi; Igase, Michiya; Ohyagi, Yasumasa; Shibata, Hiroki (Frontiers in Genetics, 2023)
Frontotemporal dementia and/or amyotrophic lateral sclerosis 6, also known as amyotrophic lateral sclerosis 14, is an autosomal dominant, progressive neurodegenerative disorder caused by various mutations in the valosin-containing protein gene. In this report, we examined a 51-year-old female Japanese patient with frontotemporal dementia and amyotrophic lateral sclerosis. The patient began noticing gait disturbances at the age of 45 years. Neurological examination at the age of 46 years met the Awaji criteria for clinically probable amyotrophic lateral sclerosis. At the age of 49 years, she tended to have poor mood and an aversion to activity. Her symptoms gradually worsened. She required a wheelchair for transport and had difficulty communicating with others because of poor comprehension. She then began to frequently exhibit irritability. Eventually, she was admitted to the psychiatric hospital because uncontrollable violent behavior throughout the day. Longitudinal brain magnetic resonance imaging revealed progressive brain atrophy with temporal dominance, non-progressive cerebellar atrophy, and some non-specific white matter intensities. Brain single photon emission computed tomography showed hypoperfusion in the bilateral temporal lobes and cerebellar hemispheres. Clinical exome sequencing revealed the presence of a heterozygous nonsynonymous variant (NM_007126.5, c.265C>T; p.Arg89Trp) in the valosin-containing protein gene, which was absent in the 1000 Genomes Project, the Exome Aggregation Consortium Database, and the Genome Aggregation Database, and was predicted to be “damaging” by PolyPhen-2 and “deleterious” using SIFT with a Combined Annotation Dependent Depletion score of 35. We also confirmed the absence of this variant in 505 Japanese control subjects. Therefore, we concluded that the variant in the valosin-containing protein gene was responsible for the symptoms of this patient.